Perbuatan Melawan Hukum Atas Lelang Jaminan Hak Tanggungan (Studi Kasus Putusan Mahkamah Agung Nomor 2715 K/PDT/2018) - Suharyeti Suharyeti (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
Abstract The decision of Supreme Court No. 48 K/Pid/2013 strengthening the decision of Medan Appellate Court No. 103/Pid.B/2012/PN-Wkb for the acquittal of defendant. The research problem of this study are on what base the judge considered to make Decision No. 63 K/Pid/2007 and whether the defendant of the Decision No. 63 K/Pid/2007 can file an application for compensation and rehabilitation. The base on what the judge of Lubuk Pakam Court of First Instance took the consideration did not follow the stipulation in the sentencing system based on the negative proving system followed by the Indonesian Criminal Codes, while the base of the consideration taken by the judge of the Appellate Court had matched the regulated sentencing system and so did the consideration taken by the judge of the Supreme Court when strengthened the decision made by the Medan Appellate Court. The limitation of the publication of the decisions made by the Medan Appellate Court and the Supreme Court and the inadequate knowledge of the society members on the decision which regulates the deadline of filing compensation and rehabilitation has caused the defendant not to be able to receive the compensation in any form it may, and the defendant cannot enjoy the rehabilitation either because there is no one announcing it but it is only written and stuck on the announcement board at the law court. Keyword: Legal Analysis, Decision of Free from All Charges, Criminal Act, Murder AbstrakPutusan Mahkamah Agung No. 48 K/Pid/2013 yang menguatkan putusan Pengadilan Negeri Waikabubak No. 103/Pid/2012 atas putusan bebas terhadap terdakwa. Permasalahan dalam penelitian ini adalah bagaimana dasar pertimbangan hakim dalam Putusan No. 48 K/Pid/2013, serta apakah terdakwa dari Putusan No. 48 K/Pid/2013 dapat mengajukan ganti rugi dan rehabilitasi.Dasar pertimbangan hakim Pengadilan Negeri Waikabubak tidak sesuai dengan ketentuan dalam system penjatuhan putusan yakni berdasarkan system pembuktian negative yang dianut KUHAP, sedangkan dasar pertimbangan hakim Pengadilan Tinggi telah sesuai dengan system penjatuhan putusan yang diatur, demikian juga dengan ketentuan penjatuhan putusan yakni dengan menjatuhkan putusan yang menguatkan putusan bebas dari Pengadilan Tinggi Waikabubak. Keterbatasan publikasi putusan Pengadilan Tinggi dan Mahkamah Agung serta kurangnya pengetahuan masyarakat tentang putusan yang mengatur batas waktu untuk mengajukan ganti rugi dan rehabilitasi, menyebabkan terdakwa tidak dapat menerima ganti rugi dalam bentuk apapun, serta tidak dapat menikmati rehabilitasi sehubungan tidak ada yang mempublikasikan selain pengumuman penetapan dalam papan pengumuman di pengadilan.Kata Kunci : Analisis Hukum, Putusan Bebas, Tindak Pidana, Pembunuhan.